2020
DOI: 10.1002/pssa.202000248
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation and Structural Optimization of Multi‐Stage Planar Thermoelectric Coolers

Abstract: How to efficiently dissipate the heat of a large-area hot source is an urgent problem to be solved in the thermal management field of electronic devices. Herein, multi-stage planar thermoelectric coolers (TECs) oriented to the efficient planar heat dissipation for large-area hot source are designed, and a comprehensive numerical analysis focusing on the cooling performance of the coolers for a heat source is performed by the finite-element methods. The effect of input current, thickness of thermoelectric legs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The black curve is the test data of Co00, and the red one is the test data of Co02, and the blue dotted line is the room-temperature value (Figure ). With the increase in working current, Δ T c increases first and then decreases ,, because of the synergistic effect from Peltier heat, Joule heat, and Fourier heat. When the working current is 0.04 A, the Δ T c of the single-leg device fabricated by Co02 reaches its maximum value (0.5 K), which is 1.5 times higher than that of the Co00 film (0.2 K).…”
Section: Resultsmentioning
confidence: 99%
“…The black curve is the test data of Co00, and the red one is the test data of Co02, and the blue dotted line is the room-temperature value (Figure ). With the increase in working current, Δ T c increases first and then decreases ,, because of the synergistic effect from Peltier heat, Joule heat, and Fourier heat. When the working current is 0.04 A, the Δ T c of the single-leg device fabricated by Co02 reaches its maximum value (0.5 K), which is 1.5 times higher than that of the Co00 film (0.2 K).…”
Section: Resultsmentioning
confidence: 99%
“…Nie et al. [ 16 ] designed a multi-stage planar TEC, and performed a comprehensive numerical analysis focusing on the cooling performance of the multi-stage planar TEC. The results showed that the optimized multi-stage planar TEC could realize a ΔT max of 8.2 K. Gross et al.…”
Section: Introductionmentioning
confidence: 99%
“…However, the electrical devices generated a high heat flux which created a harsh environment for the thin-film TECs. The large temperature gradients and thermal stresses [ 16 ] could results in the failure of the thin-film TEC and this issue should be carefully solved [ 15 , 29 , 30 ]. Some researchers demonstrated ring-shaped thermoelectric modules [ 31 , 32 ], which showed significant superiority in the performance and reliability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation